Konsep Tanggung Jawab Notaris atas Kesalahan Klausul Akta dalam Sengketa Ekonomi Syariah (Lembaga Pengembangan Kinerja Dosen, 2025)
A notary holds a significant and strategic role in supporting the state to provide legal certainty for its citizens. Through notarial services, individuals can obtain authentic deeds that serve as the strongest and most legitimate evidence of legal acts. As the law continues to evolve, One significant advancement is the rise of the sharia-based economy. which introduces a legal framework grounded in Islamic principles. This development demands notaries to adapt, especially when drafting authentic deeds based on sharia economic transactions. One important regulation in this context is the requirement that disputes arising from sharia economic activities must be resolved in the Religious Court. Therefore, the drafting of clauses in notarial deeds must comply with applicable laws and regulations. However, in practice, notaries sometimes make errors in drafting deed clauses, which may result in legal harm to the parties involved. This research seeks to offer insights into the notary's liability for inaccuracies in clauses within authentic deeds. particularly in sharia economic disputes. It explores the notary’s role in ensuring compliance with both positive law and Islamic legal principles, as well as the potential legal consequences of such errors.